Stellenwert der 67Ga-Szintigraphie in der Primärdiagnostik und Verlaufsbeurteilung opportunistischer Pneumonien bei Patienten mit AIDS - Tatsch, K.; Knesewitsch, P.; Kirsch, C.-M.; Küffer, G.; Dörner, G.; Matuschke, A.; Bogner, J.; Goebel, F. D.; Moser, E. (Nuklearmedizin - NuclearMedicine, 1988)
Opportunistic pneumonias are a life-threatening complication in patients with AIDS. Early diagnosis and therapy is necessary to improve prognosis. This study was designed to assess the value of 67Ga scintigraphy in the primary detection and follow-up of these special pneumonias. 67Ga scintigraphy was performed in 40 patients: 10 normal controls and 30 HIV-positive patients with AIDS or AIDS-related complex (ARC). 67Ga scan results were compared with current chest radiographs and the results of pathogen detection. The evaluation of positive scans was based on a quantification of the pulmonary uptake, expressed as a pulmonary/soft-tissue uptake ratio. Only 8/30 patients had a normal scan, 22/30 showed diffuse (13/22) or focal (9/22) increases of pulmonary uptake. In 7/8 patients with normal scans the chest radiograph was negative as well. The one patient with negative scan but positive chest radiograph had pulmonary Kaposi’s sarcoma. In 11/22 patients the 67Ga scan and chest radiograph were positive simultaneously. In the other 11/22 patients with positive scans chest radiographs were initially negative but showed pathology in 5 cases within 1-2 weeks. The reason for positive scans in most cases was an opportunistic lung infection; other forms of pneumonia were only observed in two cases. The defined uptake ratio demonstrated to be a highly sensitive parameter for monitoring pneumonia and the effects of therapy in follow-up studies. In conclusion, quantitative 67Ga scintigraphy proved to be a reliable and highly sensitive method for primary detection and follow-up of opportunistic pneumonias in patients with AIDS.